TECHNOLOGY OF GROWING CUCUMBER SEEDLINGS AND SELECTION OF VARIETY IN A GREENHOUSE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article analyzes scientifically based agrotechnological methods of growing cucumber (Cucumis sativus L.) seedlings in greenhouse conditions and the criteria for selecting high-yielding, stress- and disease-resistant varieties. The importance of substrate composition, biological properties of seeds, germination, optimal control of microclimate conditions (temperature, humidity, light) and mineral nutrition in the process of growing seedlings is highlighted.